Evaluation of surgery and surgical results of Baha® Attract system implantations - single centre experience of hundred twenty five cases - Gawęcki,Wojciech (2019)
Abstract Introduction: Bone-anchored hearing aids are currently well-established solutions for treatment of hearing-impaired patients. Objective: To evaluate the surgery of the Baha® Attract system, healing process and soft tissue condition after the processor activation. Methods: 125 patients implanted with the Baha® Attract system during a 3 year period in a single ENT department were analysed. Evaluated parameters comprised: details of surgery, healing process and soft tissue condition at the time of the processor activation and on subsequent follow-up visits. Results: The implantation was conducted under local anaesthesia in 96% of patients. The mean surgery time was 42 min. Soft tissue reduction was performed in 43.2% of cases; bone polishing in 23.2% and bipolar coagulation in all the cases. Healing was uneventful in 92.8%. 10 days after the surgery, pain was reported in 48% of cases. On subsequent follow-up visits, 1 month and 3 months after the surgery, pain was present in 18.4% and 2.4% of cases respectively. Similarly, numbness and paresthesia, initially reported in 84% and 15.2%, were present in 60% and 11.2% after a month, and in 17.6% and 1.6% after three months. After the processor attachment, no serious problems were observed in the analysed group during follow-up visits. However, mild redness and/or mild pain over the magnet were observed in 9.6% of patients. Conclusion: Implantation of the Baha® Attract system is an easy and safe procedure. It can be performed under local anaesthesia in adults. There are no major surgical problems or complications, and the healing process proceeds efficiently in most patients. Postoperative pain is usually mild and gradually decreases in the following months. Numbness in the operated area is frequent, but as reinnervation occurs in time, the numb patch decreases in size and finally completely disappears in most cases.